2011
DOI: 10.1590/s0100-40422011000700015
|View full text |Cite
|
Sign up to set email alerts
|

Constituintes químicos e atividade Leishmanicida de Gustavia elliptica (Lecythidaceae)

Abstract: Recebido em 21/10/10; aceito em 17/2/11; publicado na web em 15/4/11 CHEMICAL CONSTITUENTS AND LEISHMANICIDAL ACTIVITY OF Gustavia elliptica (LECYTHIDACEAE). The phytochemical investigation of the stem bark and leaves of G. elliptica provided a mixture of the norisoprenoids blumenol B and 6-epiblumenol B along with the triterpenes friedelin, as the major constituent, friedelanol, ursa-9(11),12-dien-3-ol, a-amyrin, b-amyrin, morentenol, epifriedelanol, as well as the sesquiterpenes trans-caryophyllene, a-humule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
9
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 12 publications
(19 reference statements)
4
9
0
2
Order By: Relevance
“…A previous phytochemical investigation found that the chloroform fraction of the CBE of S. grantii contained terpenes and phenolic compounds [9]. In this work, the pentacyclic triterpenes friedelin [33,34] and 3β-friedelinol [33], and the tetracyclic triterpenes euphol and lanosterol [17,18], were isolated from the CBE of S. grantii (l " Fig. 3).…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…A previous phytochemical investigation found that the chloroform fraction of the CBE of S. grantii contained terpenes and phenolic compounds [9]. In this work, the pentacyclic triterpenes friedelin [33,34] and 3β-friedelinol [33], and the tetracyclic triterpenes euphol and lanosterol [17,18], were isolated from the CBE of S. grantii (l " Fig. 3).…”
Section: Resultssupporting
confidence: 52%
“…3). The structures of the compounds were established on the basis of extensive analysis of NMR data as well as comparison with literature data [17,18,33,34] (see Spectral assignments, Supporting Information). The NMR analysis of the fractions obtained from chromatographic separation of CBE showed characteristic signals due to terpenes.…”
Section: Resultsmentioning
confidence: 99%
“…The phytochemical study of HEXF, DCMF, and EAF fractions obtained from aerial parts of ruzigrass yielded eight compounds, and the structures of the compounds were established by comparison of their spectroscopic 1D and 2D NMR data with those reported in the literature. The HEXF fraction afforded three triterpenes, friedelin ( 1 ), oleanolic acid ( 2 ) and α ‐amyrin ( 3 ), and one steroidal sapogenin, 1‐dehydrodiosgenone ( 4 ) . Friedelin ( 1 ), two glycoside phytosterols, sitosterol 3‐ O ‐glucoside ( 5 ) and stigmasterol 3‐ O ‐glucoside ( 6 ), and one flavone, tricin ( 7 ), were obtained from the DMF fraction .…”
Section: Resultsmentioning
confidence: 99%
“…Hexane eluates of several plant species from the Amazon region have shown anti-parasitic activities against Leishmania promastigotes; these include Annona foetida (20) , Garcinia brasiliensis (21) , and Lacistema pubescens (22) against L. amazonensis, Gustavia elliptica against L. braziliensis (23) , and Guarea kunthiana and Casearia sylvestris against L. donovani (24) .…”
Section: Discussionmentioning
confidence: 99%